2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8462671
|View full text |Cite
|
Sign up to set email alerts
|

Breast Density Classification with Deep Convolutional Neural Networks

Abstract: Breast density classification is an essential part of breast cancer screening. Although a lot of prior work considered this problem as a task for learning algorithms, to our knowledge, all of them used small and not clinically realistic data both for training and evaluation of their models. In this work, we explore the limits of this task with a data set coming from over 200,000 breast cancer screening exams. We use this data to train and evaluate a strong convolutional neural network classifier. In a reader s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…In a study of 6081 patients, Brandt et al showed moderate agreement, with k scores of 0.46 for Quantra and 0.57 for Volpara (13). More recently, Wu et al used a DL model to assess density in a reader study of 100 mammograms and showed moderate agreement between their DL model and the assessment of an experienced breast imager, with a k score of 0.48 (12). In contrast, our DL model showed higher agreement, with k scores of 0.67 (95% CI: 0.66, 0.68) and 0.78 (95% CI: 0.73, 0.82) in our test set and reader study, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 6081 patients, Brandt et al showed moderate agreement, with k scores of 0.46 for Quantra and 0.57 for Volpara (13). More recently, Wu et al used a DL model to assess density in a reader study of 100 mammograms and showed moderate agreement between their DL model and the assessment of an experienced breast imager, with a k score of 0.48 (12). In contrast, our DL model showed higher agreement, with k scores of 0.67 (95% CI: 0.66, 0.68) and 0.78 (95% CI: 0.73, 0.82) in our test set and reader study, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent was waived. This dataset * is a larger and more carefully curated version of a dataset used in our earlier work (14,15). The dataset includes 229,426 digital screening mammography exams (1, To extract labels indicating whether each breast of the patient was found to have malignant or benign findings at the end of the diagnostic pipeline, we relied on pathology reports from biopsies.…”
Section: Datamentioning
confidence: 99%
“…With the advent of deep learning in image processing and classification, the technique has been gaining more attention in medical image processing [34,35] worldwide for segmentation and classification processes. Various studies have been performed using deep learning for density classification resulting in promising classification models [36][37][38][39]. But most of the deep learning methods focused on binary classification (fatty or dense) of mammographic breast density.…”
Section: Introductionmentioning
confidence: 99%